Apple snail egg perivitellin coloration, as a taxonomic character for invasive Pomacea maculata and P. canaliculata, determined by a simple method - Pasquevich, María Yanina (2020)
Pomacea canaliculata and P. maculata are freshwater apple snails considered two of the most invasive alien species worldwide. They are expanding their ranges in Asia, Europe and North America, damaging crops, wetland ecosystems and endangering human health. Despite having different invasive potential, they have systematically been misidentified because of their morphological plasticity with highly variable shells, which hampers efforts to manage their spread and impact. Thus, additional work is needed to clarify species boundaries in this group of Pomacea. Here we report a new taxonomic character based on the spectroscopic characteristics of their pigmented perivitellins (egg proteins) and a fast and simple method for measuring it. The egg perivitelline fluid is analyzed via conventional agarose gel electrophoresis and the naturally-colored egg carotenoproteins are extracted, without the need for staining, and analyzed spectrophotometrically. Then, the ratio between two wavelengths (PQ) of the absorbance spectra is calculated. Results can be obtained in less than 24 h. The method was validated in the field by analysing seven populations from Asia (non-native) and South America (native) that had been genetically identified and in which PQ differed consistently between the two species. Eggs are oviposited in conspicuous reddish masses above the waterline, allowing rapid detection and easy collection of samples in the field. This novel tool would be valuable in integrative taxonomic studies to distinguish these two lineages of Pomacea and contribute to our understanding of Pomacea diversity.